Wild bees as floral visitors to Salvia assurgens (Lamiaceae): a contribution to the pollination ecology of a white-flowered endemic Mexican sage - Cultid-Medina, Carlos Andres; González-Vanegas, Paola Andrea; Bedolla García, Brenda (Instituto de Ecología, A.C., 2021)
Background and Aims: Salvia assurgens (a white-flowered sage) is considered to be a melittophilous species due to its floral architecture. However, there are no current empirical data supporting its assignment to this pollination syndrome. The present study aimed to record the diurnal floral visitors of S. assurgens to confirm its characterization as melittophilous and to evaluate which species of bees are potential pollinators. Methods: We collected wild bee visitors to the flowers of one population of S. assurgens in northeastern Michoacán, Mexico, during the summers of 2018 and 2019. We analyzed the pollen loads of each bee species and body area. In addition, we recorded the behavior of some wild bees when visiting flowers of S. assurgens. Key results: Seventeen bee species from three families (Apidae, Halictidae, and Megachilidae) were recorded as floral visitors of S. assurgens. Ninety percent of pollen carried by the examined bees belonged to S. assurgens. Four species of wild bees were the most frequent visitors, with S. assurgens accounting for 94.2% of the pollen on their bodies. Notably, these species presented clear differences in the distribution of pollen on their body parts: two of them, Bombus pennsylvanicus sonorus and Megachile sp. 1 accumulated up to 90% of the pollen on the frons and dorsal area of their thorax. It is most likely that pollen is transferred from these body areas to the stigma of S. assurgens. Conclusions: The present study provides evidence of the melittophilous pollination syndrome of S. assurgens. The wild bee richness recorded in this study is as high as that previously reported in studies on floral visitors to Neotropical sages. Finally, our results highlight the usefulness of considering pollen loads to increase our knowledge of Salvia pollination ecology.